2016
DOI: 10.1016/j.worlddev.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Violations of Conservation Rules: A Survey Experiment with Resource Users

Abstract: Small-scale corruption in government administrations that govern natural resources is believed to have a negative impact on conservation management. Yet, while corruption is said to obstruct the implementation of conservation policies, for instance as bribery may enable poaching in protected reserves, it is an underexplored area of research. This study investigates the effect of corruption, others' compliance behavior, and support for regulations on rule-violating intentions. In a betweensubjects experiment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 79 publications
1
17
0
4
Order By: Relevance
“…Such selective attitudes of governors towards fisheries regulations have an influence on the governability because it can be transmitted to fishers whose actions are also based on what they see and experience from those in governing positions. In fact, some studies have found that lack of enforcement or selective enforcement of laws and other legal instruments in natural resources management hampers conservation [26,32,53]. Thus, any attempt to tackle IUU fishing should also take into account the observed differences between stakeholder groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such selective attitudes of governors towards fisheries regulations have an influence on the governability because it can be transmitted to fishers whose actions are also based on what they see and experience from those in governing positions. In fact, some studies have found that lack of enforcement or selective enforcement of laws and other legal instruments in natural resources management hampers conservation [26,32,53]. Thus, any attempt to tackle IUU fishing should also take into account the observed differences between stakeholder groups.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, IUU fishing is a high-return activity that the offenders will continue to fish illegally as long as they gain profit. Some have also argued that weak governance, poor monitoring and enforcement, overcapacity, overfishing, and corruption can lead to unsustainable fishing behaviors [29][30][31][32]. Generally, these observations still regard IUU fishing as a legally-and instrumentally-oriented management problem, which can be tackled through a more robust set of sanctions and enforcement of fisheries regulatory measures.…”
Section: The Interactive Governance Perspective In Addressing Iuu Promentioning
confidence: 99%
“…The literature models a negative effect from small‐scale collusive corruption on the effectiveness of law enforcement: officials (e.g., rangers) may turn a blind eye to violations after being bribed (Robbins, ). Empirically, the process in which bribery hinders the implementation of regulations takes numerous shapes across natural resource types (including irrigation water, fisheries, and forests) and in different phases of extraction; it increases access for actors who collude, affects the intensity of usage from harvesters who violate limitations, makes illegal goods appear legal through the falsification of documents (e.g., in logging operations), and facilitates the smuggling of harvested goods across borders (see Smith et al., ; Sundström, , ). Yet, there are gaps in this research body.…”
Section: Research On Corruption and Natural Resource Regulationsmentioning
confidence: 99%
“…Asimismo, resulta útil para el análisis de la corrupción porque permite evitar sesgos en los resultados aplicando estímulos que facilitan tratar temas sensibles como este, lo cual no necesariamente ocurre cuando se aborda el tema directamente a través de encuestas. Los temas de los estudios desarrollados con este diseño que revisaremos son dos: i) las percepciones y actitudes hacia la corrupción (Truex, 2011) y ii) las faltas y prácticas corruptas (Sundstrom, 2016; Corbacho, Gingerich, Oliveros y Ruiz-Vega, 2016).…”
Section: E  unclassified
“…Por ejemplo, Sundstrom (2016) realiza un diseño experimental por encuesta para identificar el efecto de la corrupción sobre la propensión a incumplir normativas entre pequeños pescadores en Sudáfrica. El experimento se aplicó a una muestra de 201 pequeños pescadores, quienes fueron encuestados acerca de sus características socioeconómicas y sus actitudes y percepciones hacia el cumplimiento de las regulaciones en el sector pesquero, lo cual permitió calcular un índice que identifica el nivel de apoyo al cumplimiento de las regulaciones en el sector por parte de las pesqueras.…”
Section: Ii) Faltas Y Prácticas Corruptasunclassified